Carbon dioxide storage in the UK southern north sea: experimental and numerical analysis - Aminu, Mohammed Dahiru (Cranfield University, 2018)
This thesis contributes to the significant portfolio of research on carbon capture and storage (CCS) in general, and the potential for CO₂ storage with impurities within the UK Southern North Sea (UKSNS) to meet the global greenhouse gas emission reduction targets. First, this thesis extensively reviews the current developments in carbon dioxide storage, highlighting major options for CO₂ sequestration, storage site evaluation criteria, behaviour of CO₂ in the reservoir, methodologies for estimating storage capacity, appraisal of the major storage projects, and a projection of the future outlook for CO₂ storage. The review draws attention to the fact that although a high-quality knowledge base has been developed through CCS research, the main hinderance to CO₂ storage deployment is associated with public acceptability of the technology. Second, this thesis involves laboratory experimental investigation of the effect of impure CO₂ on reservoir grain size distributions and permeability using rock samples from the Bunter saline aquifer. The thesis shows that the presence of impurities in the CO₂ stream can affect the grain size distribution and fluid transmissivity. Third, this thesis uses numerical modelling to evaluate the effect of impure CO₂ on reservoir performance with a case study from the Bunter saline aquifer. The results show that depending on the impurities present in the CO₂ stream, the limits of stability during storage operations in saline aquifer varies, however, the variation does not affect reservoir performance negatively during long-term injection and storage.